(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2003)
Next to the journalist Líbero Badaró, Júlio Frank is one of the most lovely personalities of the academic liberal spirit. Polyglot phylosopher, he teached in Anex Curse founded the called Bucha, introducted the German Physlosophy in your country and a new wave of mistery that involves his cemetery , situated in the intern patio of the Academie.